Peran Podcast dalam Mengubah Lanskap Media Tradisional - Hasibuan, Rudi (Komunika : Jurnal Ilmiah Komunikasi, 2025)
Podcasts have become an increasingly popular phenomenon in recent years, significantly changing the traditional media landscape. With their ability to reach a global audience and provide content that can be accessed anytime, podcasts have become a serious competitor to traditional media such as radio and television Therefore, it is important to understand the role of podcasts in changing the way we consume information and entertainment. The background of this study is the need to understand the changes that are taking place in the media industry, especially due to the development of digital technology. With the advancement of the internet and mobile devices, consumers have greater access to a variety of content through podcasts, which in turn affects traditional media. By receiving this background information, it can help in assessing the impact of podcasts on the established media landscape. The research method used in this study is qualitative research. The data collection methods that will be used in this study include interviews, observations, and document analysis. The data analysis method that will be used in this study is thematic analysis. Data collected from interviews, observations, and document analysis will be analyzed inductively to identify emerging themes and patterns. The results of the research that has been conducted show that the role of podcasts in changing the traditional media landscape is very significant and has a strong impact. Podcasts have become one of the alternative media that are increasingly popular and in demand by the public quickly. This phenomenon arises because podcast content offers extraordinary flexibility for listeners to listen to content anytime and anywhere, according to their free time and interests. The conclusion of this study shows that the role of podcasts has provided new opportunities for individuals to produce and consume interesting audio content. With a flexible format and diverse content, podcasts are able to attract the attention of viewers who are looking for variety and deeper engagement.